Effect Of Organizational Commitment, Organizational Climate, And Work Safety On Turnover Intention And Job Satisfaction As Intervening Variables At PT. Karya Mitra Nugraha Semarang - Ristianawati, Yuyun; Kurniawan, Bayu (Economics and Business Solutions Journal, 2019)
The purpose of this study is to analyze organizational commitment, organizational climate, and work security on job satisfaction. Effect of organizational commitment, organizational climate, and work security on turnover intention. PT Karya Mitra Nugraha Semarang. This research is analytical, which explains the influence between research variables and facts. In this study the population is all employees of PT Karya Mitra Nugraha Semarang who are respectable 530 people. While the sample in the study was 85 people. The data analysis technique in this study is Path Analysis. The results showed that the commitment variable was positive and significant for job satisfaction, positive and significant for job satisfaction, positive and significant for job satisfaction. Negative and significant job satisfaction on turnover intention, negative and significant organizational commitment to turnover intention, organizational climate does not have a negative and significant effect on turnover intention. Negative and significant job security on turnover intention.